Invisible connections. Early Dynastic and Old Kingdom Egyptian metalwork in the Egyptian Museum of Leipzig University. (August 2018) - Kmošek, Jiří; Odler, Martin; Fikrle, Marek; Kochergina, Yulia V.
Abstract: An assemblage of ancient Egyptian metalwork from the Early Dynastic and Old Kingdom periods, currently in the Egyptian Museum of Leipzig University (Germany), has been studied using a wide range of available archaeometallurgical methods. The 3rd millennium BC Egyptian copper metallurgy is known only superficially until now. The data are interpreted in the framework of the known and reconstructed distribution networks of ancient Egyptian society. The production technology of the objects has been examined. The lead isotope analyses have made it possible to discuss the origin of the ore used for the production of Old Kingdom metalwork for the first time. A rather surprising presence in the Early Dynastic assemblage of object similar in isotopic ratios to Anatolian Early Bronze Age metalwork is discussed. Highlights: Assemblage of 22 Third Millennium BC Egyptian metal artefacts is analysed. Production technology is similar for all objects (recrystallized or wrought copper). Eastern Desert copper is remarkably frequent in the corpus. Dynasty 1 Abusir bowl was made of similar ore as CuAsNi artefacts from EBA Anatolia.